Tingkat Kompetensi Pengetahuan Perpustakaan bagi Guru Madrasah melalui Diklat Substantif Pembekalan Penugasan Tambahan Calon Pustakawan - Falak, Samsul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Teachers do have teaching education backgrounds, but many of them worked as library chief as well even though they do not posses librarianship background. All participants (library school chief candidates) do not have such a background. Hence, the study will research on it. The workshop held by Balai Diklat Keagamaan Semarang is aimed to add librarianship insights for all participants. All parcipants were given pre-test and post-test. From the pre-tes, it is found that 35% were low and 60% were in the middle, while the rest were high. Meanwhile, from the post-test the lowest was 0%, middle was 70%, and the highest was 30% respectively. The workshop is a proper medium to enhance competency for all candidates. It is shown that from the result findings that the knowledge of librarianship was significantly improved